Rancang Bangun Sistem Informasi Manajemen Proposal Kemahasiswaan - Fajar Nugraha; Muhammad Arifin; Arif Harjanto (Institut Informatika dan Bisnis Darmajaya, 2020)
Abstract The college student affairs at a university is one of the units that conducts quite a lot of student activities. The many of college student activities requires documentation of the various stages of the proposed activity proposal from various student activities. Which carries out many activities certainly requires a good planning so that the implementation of the activities proposed by college students or through representatives of student activities can proceed according to the proposed plan. Likewise, the proposal for the implementation of college student activities at the University goes through various stages so that proposals proposed by college students can be approved by the college student affairs. These activities certainly require a good planning so that the implementation of activities proposed by college students and through representatives of student activities can proceed according to the proposed plan. The number of college student activity proposal certainly requires the development of an information system that will assist the management of college student proposals. Based on this background in this study will develop an information system that can be used for management of college student activity proposals. The system development method used is prototype while the information system design method will use a unified modeling language (UML). The final result of this study is a system that can be used for the management of the submission of college student activity proposals which includes the process of data collection on various student activities, registration of proposals, approval of supervisors, evaluation of proposals and reports on the results of college student activity proposals. Keywords: Information Systems; Management, College Student Proposals Abstrak Bidang kemahasiswaan pada suatu universitas merupakan salah satu unit yang melakukan pengelolaan kegiatan - kegiatan kemahasiwaan yang cukup banyak. Banyaknya kegiatan kemahasiswaan tersebut memerlukan dokumentasi berbagai tahapan usulan proposal kegiatan dari berbagai macam kegiatan kemahasiwaaan. Kegiatan - kegiatan tersebut tentunya memerlukan sebuah perencanaan yang baik agar pelaksanaan kegiatan yang diusulkan oleh mahasiswa maupun lewat perwakilan kegiatan kemahasiswan dapat berjalan sesuai dengan rencana yang diusulkan. Banyaknya usulan proposal kegiatan kemahasiswaan tersebut tentunya memerlukan pengembangan sebuah sistem informasi yang akan membantu pengelolaan usulan-usulan proposal kemahasiswan. Berdasarkan latar belakang tersebut dalam penelitian ini akan mengembangkan sebuah sistem informasi yang dapat digunakan untuk manajemen proposal kegiatan kemahasiswaan. Metode pengembangan sistem yang digunakan adalah prototype sementara metode perancangan sistem informasi ini akan menggunakan unified modeling language (UML). Hasil akhir penelitian ini adalah sistem yang dapat digunakan untuk manajemen proses pengajuan usulan kegiatan kemahasiswaan yang meliputi proses pendataan berbagai macam kegiatan kemahasiswaan, pendaftaran usulan proposal, persetujuan dosen pembimbing, evaluasi usulan proposal serta laporan hasil usulan proposal kegiatan kemahasiswan. Kata kunci: Sistem Informasi; Manajemen; Proposal kemahasiswaan